Protection of children in armed conflicts under international law : with special reference to three Israeli wars on Gaza strip in (2008), (2012) and (2014) - Asqool, Abdalfatah Mohammed Abdalfatah (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2020)
Children are one of the most vulnerable categories during armed conflicts. Although there are several international instruments exist to protect them and civilians in general during armed conflicts, there are still many violations committing against children in several armed conflicts around the world. Between 2008 and 2014, Israel launched three wars against Gaza Strip the 2008 war, the 2012 war and the 2014 war. These three wars had caused many violations which was committed by Israeli troops against civilians and children in particular. In this regards, this dissertation aims to highlights the Israeli violations committed during the three wars in Gaza Strip, especially those against children, and analysing these violations from perspective of the International Humanitarian Law on children protection. It also aims to identify the legal characterisation of the Israeli violations under the Rome Statute of International Criminal Law in order to determine the available mechanisms for prosecuting the Israeli leaders before the International Criminal Court for the committed crimes. This dissertation which is a purely doctrinal research provides a historical overview on the Arab-Israeli conflict. It further provides an overview of the International Humanitarian Law. It also discusses whether International Humanitarian Law provides special protection for children during armed conflicts. Then, it analyses the Israeli violations committed during the three wars against civilians in general in Gaza Strip with special reference to the violations committed against children from International Humanitarian Law perspective, with a view to clarify whether Israeli forces had violated the protection of children provided by International Humanitarian Law and its other principles regarding protecting civilians in general during armed conflicts. The dissertation provides an overview of the international criminal court and children protection under the Rome Statute. It further discusses the Israeli violations of International Humanitarian Law during the three wars from the Rome Statute, to determine whether these violations constitute international crimes. In addition, it also provides discussion on the mechanisms of prosecuting the Israeli leaders before the International Criminal Court for the crimes committed in Gaza Strip during the three wars. Finally, the dissertation concludes that Israel during its three wars in Gaza Strip had already violated the principles of International Humanitarian Law in relation to children protection, as well as, the protection of civilians in general. Furthermore, the Israeli violations during Gaza wars constituted war crimes, crimes of genocide and crimes against humanity, which requires an international accountability.